Subacute ruminal acidosis reduces sperm quality in beef bulls - Callaghan, M.J.; McAuliffe, P.M.; Rodgers, R.J.; Hernandez-Medrano, J.H.; Perry, V.E.A. (American Society of Animal Science, 2016)
Breeding bulls are commonly fed high-energy diets, which may induce subacute ruminal acidosis (SARA). In this experiment, 8 Santa Gertrudis bulls (age 20 ± 6 mo) were used to evaluate the extent and duration of effects of SARA on semen quality and the associated changes in circulating hormones and metabolites. The bulls were relocated and fed in yards with unrestricted access to hay and daily individual concentrate feeding for 125 d before SARA challenge. Semen was collected and assessed at 14-d intervals before the challenge to ensure acclimatization and the attainment of a stable spermiogram. The challenge treatments consisted of either a single oral dose of oligofructose (OFF; 6.5 g/kg BW) or an equivalent sham dose of water (Control). Locomotion, behavior, respiratory rate, and cardiovascular and gastrointestinal function were intensively monitored during the 24-h challenge period. Rumen fluid samples were retained for VFA, ammonia, and lactate analysis. After the challenge, semen was then collected every third day for a period of 7 wk and then once weekly until 12 wk, with associated blood collection for FSH, testosterone, inhibin, and cortisol assay. Percent normal sperm decreased in bulls dosed with OFF after the challenge period (P < 0.05) and continued to remain lower on completion of the study at 88 d after challenge. There was a corresponding increase in sperm defects commencing from 16 d after challenge. These included proximal cytoplasmic droplets (P < 0.001), distal reflex midpieces (P = 0.01), and vacuole and teratoid heads (P < 0.001). Changes in semen quality after challenge were associated with lower serum testosterone (P < 0.001) and FSH (P < 0.05). Serum cortisol in OFF bulls tended to be greater (P = 0.07) at 7 d after challenge. This study shows that SARA challenge causes a reduction in sperm quality sufficient to preclude bulls from sale as single sire breeding animals 3 mo after the event occurred.